Ammonia-oxidizer communities in an agricultural soil treated with contrasting nitrogen sources - Habteselassie, Mussie Y.; Xu, Li; Norton, Jeanette M. (Frontiers in Microbiology, 2013)
The community of ammonia-oxidizing prokaryotes was examined in an agricultural soil treated for 6 seasons with contrasting nitrogen (N) sources. Molecular tools based on the gene encoding ammonia monooxygenase were used to characterize the ammonia oxidizer communities and their abundance. Soil DNA was extracted from soils sampled from silage corn plots that received no additional N (control), dairy waste compost (DC), liquid dairy waste (LW), and ammonium sulfate (AS) treatments at approximately 100 and 200 kg available N ha-1 over 6 years. The N treatment affected the quantity of ammonia oxidizers based on estimates of amoA by real-time PCR. Ammonia oxidizing bacteria (AOB) were higher in soils from the AS200, AS100, and LW200 treatments (2.5 x107, 2.5x107, and 2.1 x107 copies g-1 soil, respectively) than in the control (8.1x106copies/g) while the abundance of amoA encoding archaea (AOA) was not significantly affected by treatment (3.8x107copies g-1 soil, average). The ratio of AOA/AOB was higher in the control and compost treated soils, both treatments have the majority of their ammonium supplied through mineralization of organic nitrogen. Clone libraries of partial amoA sequences indicated AOB related to Nitrosospira multiformis and AOA related to uncultured Nitrososphaera similar to those described by soil fosmid 54d9 were prevalent. Profiles of the amoC-amoA intergenic region indicated that both Nitrosospira- and Nitrosomonas-type AOB were present in all soils examined. In contrast to the intergenic amoC-amoA profile results, Nitrosomonas-like clones were recovered only in the LW200 treated soil-DNA. The impact of six years of contrasting nitrogen sources applications caused changes in ammonia oxidizer abundance while the community composition remained relatively stable for both AOB and AOA.